The Expression and Function of Tubulin Isotypes in Caenorhabditis elegans - Lu, Yu-Ming; Zheng, Chaogu (Frontiers in Cell and Developmental Biology, 2022)
Microtubules, made from the polymerization of the highly conserved /-tubulin heterodimers, serve as important components of the cytoskeleton in all eukaryotic cells. The existence of multiple tubulin isotypes in metazoan genomes and a dazzling variety of tubulin posttranslational modifications (PTMs) prompted the “tubulin code” hypothesis, which proposed that microtubule structure and functions are determined by the tubulin composition and PTMs. Evidence for the tubulin code has emerged from studies in several organisms with the characterization of specific tubulins for their expression and functions. The studies of tubulin PTMs are accelerated by the discovery of the enzymes that add or remove the PTMs. In tubulin research, the use of simple organisms, such as Caenorhabditis elegans, has been instrumental for understanding the expression and functional specialization of tubulin isotypes and the effects of their PTMs. In this review, we summarize the current understanding of the expression patterns and cellular functions of the nine -tubulin and six -tubulin isotypes. Expression studies are greatly facilitated by the CRISPR/Cas9-mediated endogenous GFP knock-in reporters and the organism-wide single cell transcriptomic studies. Meanwhile, functional studies benefit from the ease of genetic manipulation and precise gene replacement in C. elegans. These studies identified both ubiquitously expressed tubulin isotypes and tissue-specific isotypes. The isotypes showed functional redundancy, as well as functional specificity, which is likely caused by the subtle differences in their amino acid sequences. Many of these differences concentrate at the C-terminal tails that are subjected to several PTMs. Indeed, tubulin PTM, such as polyglutamylation, is shown to modulate microtubule organization and properties in both ciliated and non-ciliated neurons. Overall, studies from C. elegans support the distinct expression and function patterns of tubulin isotypes and the importance of their PTMs and offer the promise of cracking the tubulin code at the whole-genome and the whole-organism level.